Origin and Suppression of the Graded Phase Distribution in Ruddlesden‐Popper Perovskite Films for Photovoltaic Application. Issue 4 (28th March 2019) - Mao, Peng; Zhuang, Jing; Wei, Yuanzhi; Chen, Ningli; Luan, Yigang; Wang, Jizheng
Abstract : Ruddlesden‐Popper perovskites (2D perovskites) show tremendous potential in photovoltaic devices for their superior stability compared with their 3D counterparts, while their lower power conversion efficiencies severely hinder their further progress for practical application. Generally, the 2D perovskite films fabricated by spin‐coating present graded distribution of 2D phases, and the small‐n phases located at the film bottom will impede the interlayer charge transport. In this work, the origin of the graded phase distribution is explained, and the roles of DMSO in Ruddlesden‐Popper perovskites film crystallization are systematically investigated. DMSO was found to homogenize the film composition, and therefore suppress the proportion of the small‐n 2D phases. Through X‐ray diffraction and grazing‐incidence wide‐angle X‐ray scattering measurements, it has been revealed that an intermediate phase is responsible for the less graded films and rationalizes the effect of DMSO in film crystallization. More importantly, solar cells with an efficiency exceeding 14% are fabricated by this facile method, which deliver good light, thermal, and ambient stability without encapsulation. These findings significantly benefit the understanding of crystal growth in 2D perovskites film and demonstrate that 2D perovskites are promising candidates for high‐performance solar cells. Abstract : In this work, the origin of the graded phase distribution in 2D perovskite films is revealed: DMSO suppresses the graded distribution effectively. An intermediate phase involved DMSO is found to be responsible for the less graded films. Solar cells with a less graded phase distribution shows an improved power conversion efficiency exceeding 14%.